Efeito do PTH tópico incrementado ao BioGran® no defeito peri-implantar em ratos submetidos à orquiectomia - Ferreira, Pedro Henrique Silva Gomes [UNESP] (Universidade Estadual Paulista (Unesp), 2020)
Objective: To evaluate PTH 1 34 in a topical way, functionalized to BioGran® by the sonochemistry technique, in peri implant d efects in rats submitted to orchiectomy. Materials and Methods: 128 rats were divided into 2 groups: SHAM fictitious surgery, ORQ orchiectomy, which each group was subdivided into 3 CLOT groups (periimplant defect, without biomaterial); BG (peri impla nt defect BioGran®); BGPTH (peri implant defect BioGran® functionalized with PTH 1 34). Each animal received an implant in the tibial metaphysis. At 14 and 42 days after surgery, calcein and alizarin fluorochromes were administered, respectively. Eutha nasia occurred at the 30th (ultrastructural and EDX analysis) and 60th day (other analyzes) after the implant installation. The samples were analyzed by immunohistochemistry ( Beta Catenin, TRAP and OC), HE and RT PCR ( ALP and OC), in addition t o biomechanical analysis, microCT for evaluation of bone volume percentage parameters BV/TV), trabecular thickness (Tb. number and separation of trabeculae (Tb. Tb.Sp) and percentage of total porosity, (Po tot) and Bone Implant Contact ( by iS). For laser confocal microscopy, the measurement of the fluorochrome area, the mineral apposition rate ( and the area of ne oformed bone area ( and elemental analysis ( At the ultrastructural analysis MET analyzes were performed. Nonparametric data were compared using the Kruskal Wallis test and parametric data using the one and two way ANOVA test. As a post test, the Holm Sidak or Tukey tests were applied, with a significance level of 5%. Results: For the microtomographic parameters referring to volume and quality (BV/ Tb.Th, Tb.Sp and Tb.N) the bio material showed improvement in all groups applied with or without PTH 1 34, for BIC it was possible to notice that the ORQ BGPH group was similar to the SHAM BG ( 0.05). For NBA and analysis of fluorochromes, the functionalized biomaterial increased the local bone regeneration of the orchiectomized animal to the same level as the healt hy animal in which biomaterial was used with or without PTH 1 34. Conclusions: The functionalization of BioGran® with PTH 1 34 shows improvement in bone regeneration in animals, being even more effective in animals submitted to osteoporosis.

Objetivo: Avaliar o PTH 1-34 em via tópico, funcionalizado ao BioGran® pela técnica da sonoquimica, nos defeitos peri-implantares em ratos submetidos à orquiectomia. Materiais e Métodos: 128 ratos foram divididos em 2 grupos: SHAM - cirurgia fictícia, ORQ - orquiectomia, os quais cada grupo destes foram subdivididos em 3 grupos CLOT (defeito peri-implantar, sem utilização de biomaterial); BG (defeito peri-implantar + utilização do BioGran®); BGPTH (defeito peri-implantar + BioGran® funcionalizado com PTH 1-34 tópica). Cada animal recebeu um implante na metáfise tibial. Aos 14 e 42 dias de pós-operatório, foram administrados os fluorocromos calceína e alizarina, respectivamente. A eutanásia ocorreu ao30o (análises ultraestrutural e EDX) e 60o dia (demais análises) após a instalação dos implantes. As peças foram analisadas pela imunoistoquímica (WNT, Beta Catenina, TRAP e OC), HE e RT-PCR (RUNX2, ALP e OC), além da análise biomecânica, microtomografia computadorizada (microCT) para avaliação dos parâmetros de percentual de volume ósseo (BV/TV), espessura do trabeculado (Tb.Th), número e separação de trabéculas (Tb.N, Tb.Sp) e percentual de porosidade total, (Po-tot) e Bone Implant Contact (BIC, pela i.S). Para microscopia confocal a laser, a mensuração da área dos fluorocromos, da taxa diária de aposição mineral (MAR), e área de osso neoformado (AON) e análise Elementar (EDX). A nível ultraestrutural foram realizadas as análise de MET. Os dados não paramétricos foram comparados pelo teste Kruskal-Wallis e paramétricos pelo teste ANOVA 1 ou 2 fatores. Como pós-teste, os testes de Holm-Sidak, ou Tukey foram aplicados, com nível de significância a 5%. Resultados: Para os parâmetros microtomográficos referente a volume e qualidade (BV/TV, Tb.Th, Tb.Sp e Tb.N) o bio material mostrou melhora em todos os grupos aplicados com ou sem PTH 1-34, já para BIC foi possível notar que o grupo ORQ-BGPH foi semelhante ao SHAM-BG (p>0,05). Para AON e analise dos fluorocromos a o biomaterial funcionalizado elevou a regeneração óssea local do animal orquiectomizado ao mesmo nível do animal saudável em que foi utilizado biomaterial com ou sem PTH 1-34. Conclusões: A funcionalização do BioGran® com PTH 1-34 apresenta melhora na regeneração óssea dos animais, sendo ainda mais eficaz nos animais submetidos a osteoporose.
Effect of topical PTH added to BioGran® on peri-implant defect in rats submitted to orchiectomy
Keywords: Osteoporosis; Dental implants; Osteoporose; Regeneração óssea; Hormônio paratireóideo; Implantes dentários